2012
DOI: 10.1016/j.quascirev.2012.09.021
|View full text |Cite
|
Sign up to set email alerts
|

A pluvial episode identified in arid Australia during the Medieval Climatic Anomaly

Abstract: Optically stimulated luminescence (OSL) ages from a relict shoreline on Lake Callabonna record a major pluvial episode in southern central Australia between 1050 ± 70 and 1100 ± 60 Common Era (CE), within the Medieval Climatic Anomaly (MCA). During this pluvial interval Lake Callabonna filled to 10-12 times the volume of the largest historical filling (1974) and reached maximum depths of 4-5 m, compared to the 0.5-1.0 m achieved today. Until now there has been no direct evidence for the MCA in the arid interio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…Pit SC5A). Thus the combined geomorphic, chronological, and soil chemical observations for the soils exposed in Pits SC6A and SC5A appear to provide pedogenic evidence supporting the occurrence of regional late Holocene wet phases Cohen et al, 2011;Cohen et al, 2012a;Cohen et al, 2012b;Gliganic et al, 2014).…”
Section: Implications For Palaeoenvironmental Controls On Pedogenesismentioning
confidence: 76%
See 2 more Smart Citations
“…Pit SC5A). Thus the combined geomorphic, chronological, and soil chemical observations for the soils exposed in Pits SC6A and SC5A appear to provide pedogenic evidence supporting the occurrence of regional late Holocene wet phases Cohen et al, 2011;Cohen et al, 2012a;Cohen et al, 2012b;Gliganic et al, 2014).…”
Section: Implications For Palaeoenvironmental Controls On Pedogenesismentioning
confidence: 76%
“…2, 3c, Table 1; Cohen et al, 2012a). Two stratigraphic units composed of partially landward dipping high-energy beach sands and gravel were observed in Pit SC6A (Figs.…”
Section: Topography Sediments and Chronostratigraphymentioning
confidence: 91%
See 1 more Smart Citation
“…The larger arid-zone lake systems also record a long history of fluctuating climate with the work of Magee et al (2004) and Cohen et al (2011Cohen et al ( , 2012a all demonstrating that these inland catchments were much wetter about 100,000-50,000 years ago than at present with the presence of large "megalakes" and associated Pleistocene megafauna (Webb, 2010). Even more recently in the geological past (e.g., the medieval climatic anomaly, ∼1000 years ago) it has been shown that the Lake Frome-Callabonna system experienced exceptionally wet events that produced aggradational evidence of past lake filling (Cohen et al, 2012b;Gliganic et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…The finite mixture model (FMM) can be used to identify discrete D e components within a distribution Galbraith and Roberts, 2012), and it has been used to elucidate OSL chronologies in complex archaeological (David et al, 2007;Jacobs et al, 2008;Lombard et al, 2010;Gliganic et al, 2012), aeolian (Lomax et al, 2011), shoreline (Cohen et al, 2011(Cohen et al, , 2012a, fluvial (Rodnight et al, 2005), and glacial (Duller, 2006) settings. In environments where postdepositional mixing by pedoturbational processes (e.g., bioturbation or argilliturbation; Hole, 1961;Johnson et al, 1987;Schaetzl and Anderson, 2005) is particularly prevalent however, obtaining a depositional age is still challenging (Feathers et al, 2006;Bateman et al, 2007b;Rhodes et al, 2010;Tribolo et al, 2010;Chazan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%